KOLABORASI UNIVERSITAS NEGERI MALANG DENGAN PERHIMPUNAN PELAJAR INDONESIA (PPI) TAIPEI DALAM PELATIHAN DIGITAL MARKETING UNTUK BURUH MIGRAN DI TAIWAN - Aripriharta, Aripriharta; Wibawa, Aji Prasetya; Andriansyah, Muhammad Rizal; Nasih, Ahmad Munjin; Purwatiningsih, Ayu; Faidzin, Ilham; Bagaskoro, Muhammad Cahyo (Universitas Padjadjaran, 2024)
The collaboration between PPI Taipei and UM aims to equip migrant workers in Taiwan with digital marketing skills that are essential in the global era. The challenges of fierce competition in the job market demand an understanding of business technology. However, limited access and resources are obstacles for them to acquire these skills. To address this,